Redesigning Non-Academic Employee Compensation System of School of Business and Management (SBM) ITB - Dwi Putri, Yuti; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2012)
Compensation system of School of Business and Management (SBM), Institut Teknologi Bandung (ITB), covers lecturers and non-academic employees’ compensation system. The system that regulates non-academic employees has not met the criteria of internal equity and external competitiveness. The current compensation system is also likely to apply the model of 100% fixed salary, so it has not been able to encourage employee motivation to perform at the maximum. Therefore, it is necessary to evaluate and redesign the implemented compensation system of SBM ITB from the internal point of view. To capture the business issue, questionnaire distribution and FGD activity were conducted on 30 representative employees concerning internal equity, external competitiveness, employee contributions, management of the pay system, and budget capabilities. The results reveal that employees felt dissatisfied with the payroll components and also questioned about the existence of communication forum to facilitate information sharing and grievances. The possible alternative solutions are applying person-based compensation model considering the educational background and job experience as the entry level criteria, job-based compensation model, and adjustable benefit alocation with specific payroll components of each and also reinforcing the communication forum for employees. Keywords: compensation system, person-based compensation model, job-based compensation model, benefit, payroll